Analisis Teologis tentang Pertahanan Rohani dan Kekuatan Doa dalam Efesus 6:14-20 - Daniel Ari Wibowo; Meniati Hia (Jurnal Missio Cristo, 2023)
This study examines the theological aspects of spiritual defense and the power of prayer found in the text Ephesians 6:14-20. This text portrays the spiritual armor that every believer must put on to combat evil forces and face challenges in the Christian life. A thorough analysis of this armor, such as the belt of truth, the shoes of readiness, the shield of faith, the helmet of salvation, and the sword of the Spirit, provides insights into how believers can resist the deceptions of the Devil and stand firm in their faith. Furthermore, this study also explores the significance of prayer in spiritual warfare and how various types of prayers and petitions can strengthen faith and enhance the ministry of the church. Through a theological analysis of this text, this research offers a deeper understanding of the importance of spiritual armor and prayer in confronting spiritual challenges in the Christian life. The theological implications of this text are also evaluated in the context of salvation theology and the relationship with the Holy Spirit. The results of this study will provide guidance for the church and individuals in activating their spiritual defense and harnessing the power of prayer to face the spiritually challenging world. ABSTRAK BAHASA INDONESIA Studi ini menganalisis teologis tentang pertahanan rohani dan kekuatan doa yang terdapat dalam teks Efesus 6:14-20. Teks ini menggambarkan perlengkapan perang rohaniah yang harus dikenakan oleh setiap orang percaya untuk melawan kekuatan jahat dan menghadapi tantangan dalam hidup Kristen. Analisis mendalam tentang perlengkapan tersebut, seperti sabuk kebenaran, sepatu kesediaan, perisai iman, helm keselamatan, dan pedang Roh, memberikan wawasan tentang bagaimana orang percaya dapat menghadapi tipu daya Iblis dan berdiri teguh dalam iman. Selain itu, studi ini juga mengeksplorasi pentingnya doa dalam pertempuran rohaniah dan bagaimana berbagai jenis doa dan permohonan dapat memperkuat iman dan memperkuat pelayanan gereja. Melalui analisis teologis terhadap teks ini, penelitian ini memberikan pemahaman yang lebih mendalam tentang pentingnya perlengkapan rohaniah dan doa dalam menghadapi tantangan spiritual dalam kehidupan Kristen. Implikasi teologis dari teks ini juga dievaluasi dalam konteks teologi keselamatan dan hubungan dengan Roh Kudus. Hasil penelitian ini akan memberikan panduan bagi gereja dan individu dalam mengaktifkan pertahanan rohani dan memanfaatkan kekuatan doa untuk menghadapi dunia roh yang penuh tantangan.